Oxidation of organic molecules with a redox-Active guanidine catalyst - Wild, Ute; Schön, Florian; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2017)
Herein, we report the first examples of the use of redox-active guanidines as catalysts in the green oxidation of organic molecules with dioxygen. In one half-reaction, the oxidized form of the redox-active guanidine is converted into the reduced, protonated state, thereby enabling dehydrogenative oxidation of the substrate (3,5-di-tert-butylcatechol→ortho-benzoquinone, benzoin→benzil, and 2,4-di-tert-butylphenol→biphenol). In the other half-reaction, efficient re-oxidation of the guanidine to the oxidized state is achieved with dioxygen in the presence of a copper catalyst. These results pave the way for the broader use of redox-active guanidines as oxidation catalysts.